Macroaggregates Serve as Micro-Hotspots Enriched With Functional and Networked Microbial Communities and Enhanced Under Organic/Inorganic Fertilization in a Paddy Topsoil From Southeastern China - Rui, Zhipeng; Lu, Xinda; Li, Zichuan; Lin, Zhi; Lu, Haifei; Zhang, Dengxiao; Shen, Shengyuan; Liu, Xiaoyu; Zheng, Jufeng; Drosos, Marios; Cheng, Kun; Bian, Rongjun; et al. (Frontiers in Microbiology, 2022)
Microbial communities of soil aggregate size fractions were explored with molecular and networking assays for topsoil samples from a clayey rice paddy under long-term fertilization treatments. The treatments included no fertilizer (NF) as control, chemical fertilizer only (CF), chemical fertilizer with swine manure (CFM), and chemical fertilizer with rice straw return (CFS). Following a wet-sieving protocol, water stable aggregates were separated into size fractions of large macroaggregates (L-MacA, >2000 μm), macroaggregates (MacA, 2000-250 μm), microaggregates (MicA, 250-53 μm), fine microaggregates (F-MicA, 53-2 μm) and fine clay (F-Clay, <2 μm). Mass proportion was 32.3-38.2% for F-MicA, 23.0-31.5% for MacA, 19.0-23.1% for MicA, 9.1-12.0% for L-MacA and 4.9-7.5% for F-Clay, respectively. The proportion of MacA was increased but F-Clay was reduced by fertilization while the mean weight diameter (MWD) was increased by 8.0-16.2% from 534.8 μm under NF to 621.5 μm under CFM. Fertilization affected bacterial 16S rRNA and fungal 18S rRNA gene abundance in F-MicA and F-Clay but not in aggregates in size larger than 53 μm. However, bacterial and fungal community α-diversities and community structures were quite more divergent among the fertilization treatments in all size fractions. Organic carbon, gene abundance of bacteria and fungi were enriched in both L-MacA and MacA but depleted in F-Clay, while microbial Shannon diversity was rarely changed by fraction size under the four treatments. L-MacA and MacA contained more bacteria of r-strategists and copiotrophs while F-MicA and F-Clay were demonstrated with a higher abundance of K-strategists and oligotrophs. Guilds of parasitic and litter saprotrophic fungi were enriched in F-MicA but depleted in L-MacA. Furthermore, most of bacterial and fungal OTUs were strongly interacted in L-MacA and MacA rather than in MicA and F-Clay. Thus, macroaggregates acted as micro-hotspots enriched with functional and networked microbial communities, which were enhanced with organic/inorganic fertilization in the rice paddy.